The Role of Third-Party Logistics (3PL) Providers’ Competence in Enhancing Supply Chain Performance: A Dynamic Capability and Relational View Analysis in Ghana’s Cocoa Industry - Agyenim-Boateng, George (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study explores the role of Third-Party Logistics (3PL) providers' competence in enhancing organisational performance within Ghana's cocoa industry, using the Relational View (RV) and Dynamic Capability Theory (DCT) as frameworks. It investigates how logistics integration—through internal and external information sharing, IT capabilities, and resource sharing—impacts 3PL competence and organisational performance. A quantitative approach was employed, with data collected from 989 stakeholders in Ghana's cocoa supply chain, including Licensed Buying Companies (LBCs), haulage providers, and warehousing firms. Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) were used to analyze the data. Results show that logistics integration significantly enhances 3PL competence, which in turn improves organisational performance. External IT capabilities had the strongest positive relationship with 3PL competence (β = 0.245, p < 0.001), followed by internal IT capabilities (β = 0.176, p < 0.001) and external information sharing (β = 0.217, p < 0.001). Transportation sharing, however, did not significantly influence 3PL competence (β = 0.018, p = 0.356). The study concludes that 3PL competence is a critical mediator between logistics integration and organisational performance, emphasizing the importance of strong 3PL partnerships, IT investments, and effective information sharing. It also validates the complementary roles of RV and DCT in explaining how relational mechanisms and dynamic capabilities drive success in complex environments. Recommendations include enhancing 3PL competence through provider selection, IT investments, and policy support, while future research should explore other industries, advanced technologies, and longitudinal impacts.